The evolution of swidden fallow secondary forests in Asia - Jong, W. de; Chokkalingam, U.; Perera, G.A.D. (2001)
Swidden agriculture in tropical Asia is a diverse practice, making it difficult to draw general conclusions on trends of the development of swidden fallow secondary forests (SFSF). There is, however, sufficient evidence to recognise trends of a gradual intensification often through the incorporation of extensive tree crop production in SFSF, or a direct conversion to intensive tree cash cropping. Factors contributing to the changes include emerging markets for cash crops or timber and pulp wood production, government policies and development projects, fire, and population pressures. In Indonesia and mainland Southeast Asia, there is evidence of change towards tree and cash crop based production systems. In northeastern India, there is improved fallow management to sustain or enhance productivity of the shortened swidden agricultural cycle to support a subsistence economy. In Sri Lanka, biophysical factors inhibit the development of intensive agroforestry systems. Although swidden fallow land use has often been stigmatised as leading to forest decline and a related decline in the environmental functions that forests provide, there is sufficient evidence suggesting that conversion of a SFSF dominated landscape to more intensive tree cropping can have a negative environmental impact. Some general options for the evolution of swidden agriculture under different stages of a land use intensification model are considered.